Breaking Barriers: Academic Women's Leadership in Saudi Universities under Vision 2030 - ALQahtani, Munirah Sarhan (Journal of Ecohumanism, 2025)
Saudi 's Vision 2030 has catalyzed significant social and economic transformations, particularly in promoting gender inclusion and women's leadership in various sectors, including academia. Despite these advancements, female academics in Saudi universities continue to face institutional, cultural, and systemic barriers that limit their leadership opportunities. This study explores the challenges and enablers affecting academic women's leadership within Saudi universities, focusing on the impact of cultural norms, institutional policies, and government initiatives. Using a qualitative approach, semi-structured interviews were conducted with 12 female academics to gain insights into their leadership experiences, aspirations, and obstacles. The findings highlight persistent gender disparities, structural barriers, and the role of Vision 2030 in fostering change. While governmental and institutional reforms have facilitated progress, additional efforts are needed to ensure equitable leadership opportunities for women in academia.